2012
DOI: 10.1093/jxb/ers194
|View full text |Cite
|
Sign up to set email alerts
|

The peach (Prunus persica L. Batsch) genome harbours 10 KNOX genes, which are differentially expressed in stem development, and the class 1 KNOPE1 regulates elongation and lignification during primary growth

Abstract: The KNOTTED-like (KNOX) genes encode homeodomain transcription factors and regulate several processes of plant organ development. The peach (Prunus persica L. Batsch) genome was found to contain 10 KNOX members (KNOPE genes); six of them were experimentally located on the Prunus reference map and the class 1 KNOPE1 was found to link to a quantitative trait locus (QTL) for the internode length in the peach×Ferganensis population. All the KNOPE genes were differentially transcribed in the internodes of growing s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
45
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(51 citation statements)
references
References 86 publications
(116 reference statements)
6
45
0
Order By: Relevance
“…The loss-of-function mutants fail to maintain shoot meristems [16][17][18]. In addition, class I KNOX genes are involved in distinct aspects of developmental processes, such as leaf dissection in compound leaf species, internode elongation, inflorescence architecture and establishment of vascular connections between parasitic plants and their hosts [19][20][21][22][23][24]. Thus, the class I KNOX gene regulatory module has been recruited to various developmental processes during the evolution of shoot systems.…”
Section: Diverse Functions Of Knox Genes In the Plant Lineagementioning
confidence: 99%
“…The loss-of-function mutants fail to maintain shoot meristems [16][17][18]. In addition, class I KNOX genes are involved in distinct aspects of developmental processes, such as leaf dissection in compound leaf species, internode elongation, inflorescence architecture and establishment of vascular connections between parasitic plants and their hosts [19][20][21][22][23][24]. Thus, the class I KNOX gene regulatory module has been recruited to various developmental processes during the evolution of shoot systems.…”
Section: Diverse Functions Of Knox Genes In the Plant Lineagementioning
confidence: 99%
“…In Arabidopsis, a mutation in the second enzyme (C4H) of lignin biosynthesis pathway decreased levels of several different classes of phenylpropanoid end products and exhibited reduced lignin deposition, altered lignin monomer content, and a collapsed xylem phenotype (Schilmiller et al 2009). In this context of cross talk between establishment and development of the cambium meristem on the one hand and lignification on the other, it is interesting to note that a class I knotted-like gene (knope1) prevented cell lignification by repressing lignin genes during peach stem primary growth (Testone et al 2012), suggesting the role of knox genes in suppressing lignin biosynthesis during storage root formation in sweet potato.…”
Section: F Lignification Of Sweet Potato Roots and Related Gene Exprmentioning
confidence: 99%
“…The expression pattern of CCOMT and CAD indicated that lignin biosynthesis was reduced during the early stage of SR development. In addition, upregulation of KNOX1 in I-stage and S-stage was negatively correlated with the expression of lignin biosynthesis key genes (CCOMT and CAD) (Guo et al 2001;Townsley et al 2013) suggesting that reduction of lignin biosynthesis corresponds to SR development (Firon et al 2013;Testone et al 2012).…”
Section: Functional Analysis Of Significant Genes During Phase Transimentioning
confidence: 99%